Immunotherapy with depigmented-polymerized mixed tree pollen extract: a clinical trial and responder analysis - Pfaar, Oliver; Robinson, D. S.; Sager, A.; Emuzyte, R. (Allergy, 2010)
Background: Rhinoconjunctivitis because of tree pollen sensitization is common in Northern Europe. Specific subcutaneous immunotherapy (SCIT) is the only disease-modifying treatment, but unmodified allergen extracts carry a risk of allergic side-effects. Our objective was to examine efficacy and safety of a depigmented-polymerized mixed tree pollen extract. Methods: A double-blind, placebo-controlled trial of 184 tree pollen allergic adults was performed. SCIT consisted of four increasing doses at 7-day intervals, then maintenance injections every 6 weeks for 18 months. Primary outcome was combined symptom and medication score during the 2008 season. Secondary outcomes included analysis at different levels of pollen exposure and a responder analysis. Adverse events were classified using the EAACI scale. Birch pollen-specific IgE and IgG4 were measured before and after treatment. Results: The combined symptom and medication score of actively treated patients was significantly lower than those on placebo (P < 0.04). Increased efficacy was seen at high pollen exposure (median score 2.1 for active [IQR 0.7-3.4] vs 4.2 [IQR 2.4-5.3] for placebo for days with 500 or more pollen grains per m3, a 50% reduction, P < 0.01). A modified responder analysis revealed 64% responders in the active and 32% in the placebo group (P < 0.01). There were 17 systemic reactions. All were mild (grade 1 or 2) and required no treatment. Serum birch-specific IgG4 increased in the SCIT group (P < 0.01). Conclusions: SCIT with depigmented- polymerized tree pollen extract was clinically effective and well tolerated. Responder analysis suggested that one-third of patients treated with immunotherapy may not respond.
Gesehen am 28.04.2023